The various contours of the inmunity of jurisdiction in the field of the individual employment contract (the decision of the Higher Court of Madrid of July 13, 2020) - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Analysis of the reasons and implications of judgment nº 558/2020, issued by the Court of Justice of Madrid on July 13, where it recognizes the immunity of jurisdiction of the Embassy of Brazil in Madrid in the event of a dispute arising from the claim for null dismissal filed by a worker who performed the functions of administrative assistant. With the legal basis of LO 16/205, on privileges and immunities of foreign States, the court confirms the correctness of the judgment of instance by declaring that bien a litigation that may eventually lead to the reinstatement of the worker, it incurs one of the legal excepciones to the limitation of immunity, so the that the State of Brazil can avoid the protescution of the matter by the Spanish labor courts. This raises the question of delimiting what are the contours of immunity from jurisdiction in the área of the individual employment contract. Taking into account the current Spanish regulation, it seems closer to absolute immunity than restricted.